2017
DOI: 10.3389/fimmu.2017.00563
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Cellular and Molecular Microenvironment Is Present in Tertiary Lymphoid Organs of Patients with Spontaneous Prostate Cancer Regression

Abstract: ObjectiveMultiple solid cancers contain tertiary lymphoid organs (TLO). However, it is unclear whether they promote tumor rejection, facilitate tumor evasion, or simply whether they are a byproduct of chronic inflammation. We hypothesize that although chronic inflammation induces TLO formation, the tumor milieu can modulate TLO organization and functions in prostate cancer. Therefore, our study seeks to elucidate the cellular and molecular signatures in unique prostatectomy specimens from evanescent carcinoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 85 publications
(105 reference statements)
1
40
0
Order By: Relevance
“…3e, f and S5c). Consistent with our previous report [21] and clinical PCa [22], stromal tertiary lymphoid aggregates were present in murine tumours (Fig. S5b), neither the total area of these structures nor markers of Bcell response were unaltered (Figs.…”
Section: Increased Brf1 Accelerates Prostate Tumourigenesis In Vivosupporting
confidence: 92%
See 1 more Smart Citation
“…3e, f and S5c). Consistent with our previous report [21] and clinical PCa [22], stromal tertiary lymphoid aggregates were present in murine tumours (Fig. S5b), neither the total area of these structures nor markers of Bcell response were unaltered (Figs.…”
Section: Increased Brf1 Accelerates Prostate Tumourigenesis In Vivosupporting
confidence: 92%
“…It is recognised that immune infiltration can have a significant influence upon clinical outcome in cancer patients [22]. Our previous study found that improved survival upon genetic loss of Erk5 in Pten Δ/Δ PCa model was related to increased levels of the T cell recruiting cytokines Ccl5 and Cxcl10 and enhanced T cell infiltration (predominantly CD4 + ) within the tumours [21].…”
Section: Discussionmentioning
confidence: 97%
“…In MPM, lymphoid aggregates are present in about 70% of tumors, and GCs within these aggregates can be spotted in about 30% of cases [23]. These aggregates show functional similarity to TLSs, in which T-and B-lymphocytes are apart in two adjacent regions surrounded by HEV, as already shown in ovarian and prostate cancer [93,94]. Despite that, clear evidence of HEV's presence in MPM is still lacking.…”
Section: Tertiary Lymphoid Structures In Solid Tumors and Mpm: Where mentioning
confidence: 93%
“…Within most SLOs and TLOs the basic stromal building blocks are fairly consistent, having T‐cell zones with adjacent B‐cell follicles marked within a supporting reticulum, infiltrating vascular ECs and/or LECs in the form of well‐defined vessels. Less well‐formed TLOs have lesser anatomical organization, albeit with similar building blocks, such as those found conjointly with tumors, forming a unique tumor immune microenvironment. The ultimate goal of recreating immune microenvironments, in parts or whole, is to increase knowledge in immunology or immune response by providing test platforms for mechanistic investigations.…”
Section: Conclusion and Perspectives For The Futurementioning
confidence: 99%